2013
DOI: 10.1002/zoo.21084
|View full text |Cite
|
Sign up to set email alerts
|

Apparent total tract macronutrient and energy digestibility of 1- to- 3-day-old whole chicks, adult ground chicken, and extruded and canned chicken-based diets in African wildcats (Felis silvestris lybica)

Abstract: Our objectives were to evaluate the composition of whole 1- to- 3-day-old chicks (Whole), ground adult chicken (Ground), chicken-based canned diet (Canned), and chicken-based extruded diet (Extruded); and evaluate apparent total tract energy and macronutrient digestibility of these diets by four captive African wildcats (Felis silvestrus lybica) utilizing a Latin Square design. We analyzed diets for macronutrient and mineral (Ca, P, K, Na, Mg, Fe, Cu, Mn, Zn, and S) composition, and screened for potentially pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 37 publications
1
10
0
Order By: Relevance
“…While these data indicate that mineral replete whole prey are commercially available, to determine if mineral concentrations consistently meet or exceed recommendations further analysis are necessary. Researchers have reported mineral concentrations below domestic cat recommendations (low Cu, Mn, and K concentrations) for whole prey items, including mice, rats, and quail [Clum et al, 1996, 1997; Dierenfeld et al, ; Kerr et al, ]. Similar to data reported herein, not all whole prey analyzed in those studies were below AAFCO [] recommendations.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…While these data indicate that mineral replete whole prey are commercially available, to determine if mineral concentrations consistently meet or exceed recommendations further analysis are necessary. Researchers have reported mineral concentrations below domestic cat recommendations (low Cu, Mn, and K concentrations) for whole prey items, including mice, rats, and quail [Clum et al, 1996, 1997; Dierenfeld et al, ; Kerr et al, ]. Similar to data reported herein, not all whole prey analyzed in those studies were below AAFCO [] recommendations.…”
Section: Discussionsupporting
confidence: 70%
“…Because of this variation, species‐specific differences are not readily predictable. Few researchers have performed in‐depth examinations of nutrient composition of commonly fed whole prey [Davidson et al, ; Douglas et al, ; Dierenfeld et al, ; Clum et al, ; Kerr et al, ; Kerr et al, submitted‐a], with little attention paid to commercially available frozen whole prey. A large portion of data on whole prey comes from anecdotal, unpublished, or non‐peer reviewed sources [Powers et al, ], or primarily focuses on non‐nutritive aspects [Bond and Lindburg, ; Shepardson et al, ; Ziegler, ].…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that most limiting nutrients in meat diets of exotic cats were copper, iodine, vitamin A, and vitamin E (Ullrey & Bernard, ). Ground chicken or whole chick fed to African wild cats supplied only 2 and 4 mg/kg DM of Cu (Kerr, Morris, Burke, & Swanson, ). Whole prey samples had Cu concentration below NRC () recommendation for domestic cat.…”
Section: Discussionmentioning
confidence: 99%
“…For example, commercially available 1–3-d-old chicks (CHI) are approximately 72–76 % CP, 16–20 % fat and <5 % nitrogen-free extract ( 14 , 15 ) . Previous studies have shown that extruded and whole-prey diets differ in digestibility as well as macronutrient composition ( 14 17 ) , and this may alter the fermentable substrates that are available to the gastrointestinal microbiota for fermentation ( 18 , 19 ) . The objective of the present study was to compare the faecal microbiota of cats fed an EXT chicken-based diet to those fed commercially available whole CHI.…”
mentioning
confidence: 99%